Recent near-Earth supernovae probed by global deposition of interstellar radioactive (60)Fe - Wallner, A. (Nature, 2016)
The rate of supernovae (SNe) in our local galactic neighborhood within a distance of ~100 parsec from Earth (1 parsec (pc)=3.26 light years) is estimated at 1 SN every 2-4 million years (Myr), based on the total SN-rate in the Milky Way (2.0±0.7 per century(1,2)). Recent massive-star and SN activity in Earth’s vicinity may be evidenced by traces of radionuclides with half-lives t(1/2) ≤100 Myr(3-6), if trapped in interstellar dust grains that penetrate the Solar System (SS). One such radionuclide is (60)Fe (t(1/2)=2.6 Myr)(7,8) which is ejected in supernova explosions and winds from massive stars(1,2,9). Here we report that the (60)Fe signal observed previously in deep-sea crusts(10,11), is global, extended in time and of interstellar origin from multiple events. Deep-sea archives from all major oceans were analyzed for (60)Fe deposition via accretion of interstellar dust particles. Our results, based on (60)Fe atom-counting at state-of-the-art sensitivity(8), reveal (60)Fe interstellar influxes onto Earth 1.7–3.2 Myr and 6.5–8.7 Myr ago. The measured signal implies that a few percent of fresh (60)Fe was captured in dust and deposited on Earth. Our findings indicate multiple supernova and massive-star events during the last ~10 Myr at nearby distances ≤100 pc.